FENOMENA LAPAK MESUM Di KAWASAN WISATA GRONGGONG KABUPATEN CIREBON SEBAGAI TEMPAT PERGAULAN BEBAS Di KALANGAN REMAJA. - Yeni Wahyuni * (Dimensia: Jurnal Kajian Sosiologi, 2012)
Behavior promiscuity now this can be done by anyone, anytime and anywhere, including  the  one  in  the  area  of tourism.  In  tourist  areas  often  appeared  behavioral Gronggong promiscuity among teenagers. This study aims to: 1). Describe the factors that cause a nasty stall in the area of tourism can be a region Gronggong promiscuity among  teenagers,  2).  The  effort  to  control  local  government  officials  in  tourism mentertibkan Gronggong of behavior promiscuity among teenagers.This study uses qualitative research methods with the  primary  data sourceconsists of the visitors, the traders in the Area Tourism Gronggong, PP Satpol Cirebon District, the  Village  Head Patapan Cirebon, Cirebon  District Head  of Tourism, andCommunities around Gronggong tourist area, while for source secondary data obtainedthrough documentation, literature study using books, and print media. Data collection techniques used include observation, interviews, and documentation. The  subjects inthis study were the visitors and the traders in the tourist areas Gronggong with 4 stalltraders.  The  technical  validity  of  the  data  in  this  study  using  the  technique  oftriangulation  of  sources  and  methods.  In  the  data  analysis  techniques  using  the interactive analysis of Miles and Huberman.The  results  obtained  are  the  factors  that  cause  a  nasty  stall  in  the  area  of tourism can be a region Gronggong promiscuity among teenagers consists of: 1). Nonphysical  factors  consist of  building  construction  shanties.  Shanties  located  on  the  left path has  an  insulated  building,  located  there  under  (the  category is  not  visible),  stall located on the right road in the form of benches scattered, and many benches that are built  on  a  hill  standing  upright.  The  lack  of  lighting  (illumination).  While  physicalfactors  consist  of  a  dynamic  social  relations  between  traders  and  visitors  Gronggong tourist  area,  and  factors  of  social  control  of  local  government  officials  are  less  than optimal.  2).  The  effort  to  control  local  government  officials  in  tourism  mentertibkan Gronggong  of  promiscuity  behaviors  among  adolescents  such  as  by  recording  the location  then  the  insulated,  provide  guidance,  socialization,  and  in  its  supervision  on patrol every single week, right the situation is done at a certain time and depending on the needs , as before the religious holidays, and towards the end of the year.Keywords: Phenomenon bawdy shanties, adolescents, and control